Kesuksesan Penerapan Sistem Informasi Akuntansi, Sistem Pengendalian Internal dan Kualitas Laporan Keuangan - O. Feriyanto (STIE STEMBI Bandung Business School, 2014)
The purpose of this study is explain how effect of implementation success accounting information system (quality system, use, user satisfaction, individual impact, organizational impact), internal control system (control environment, risk assessment, control activities, information and communication system, monitoring) to quality financial statement (relevance, reliable, camparability perceivable) in public hospital type b in West Java. In order to develop theoretical framework to produce hypothesis: (1) Implementation Sucdicess of Accounting Information System and Internal Control System to Financial Statement Quality on simultan. (2) Implementation Success of Accounting Information System and Internal Control System to Financial Statement Quality on partial. By using path analysis simultaneously obtained results are positive and significant influence between the success of the application of the accounting information system and the system of internal control over financial reporting quality of 70.2 % . While the partial application of the accounting information system in a positive and significant effect on the quality of the financial statements of 35.5 % . system of internal control is a significant positive effect on the quality of the financial statements of 34.7 % .